The Role of Strategic Management Accounting at PT Bank Jawa Barat TBK in Supporting the Achievement of SDG’S in West Java Province - Dewi DJUMIYATI; Imanuel SUWONGSO; Yanuar RAMADHAN (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study discusses the implementation of the Sustainable Development Goals (SDGs), specifically SDGs 1 (No Poverty) and SDGs 8 (Decent Work and Economic Growth). The purpose of this study is to provide recommendations for company management in supporting poverty alleviation and the provision of decent work and economic growth through job creation and collaboration with local governments. The approach used is descriptive analysis with a literature study method at PT Bank Jawa Barat from 2022-2024 in West Java Province. The results of the study indicate that PT Bank Jawa Barat has consistently implemented SDGs 1 and SDGs 8. The limitation of this study lies in the scope of the research, which only covers West Java Province. The implications of this study indicate that Bank BJB's contribution to achieving the SDGs has the potential to increase public, investor, and government trust and encourage sustainable regional development.